Scenario Simulation and Prediction of Land Use Patterns in Guilin City Considering Impact of Scenic Spot Expansion - Wu Zhenhua; Yu Qinping; Wang Yabei; Bai Qingguo (Shuitu baochi tongbao)
[Objective] The impact of scenic spot expansion on the land use pattern of Guilin City, Guangxi Zhuang Autonomous Region was analyzed in order to provide a theoretical reference for coping with the risks brought by a surge in tourism demand, leading to reasonable urban land planning and scientifically guiding the development of tourism. [Methods] The nuclear density analysis method and the future land use simulation (FLUS) model were used to predict and simulate the land use pattern of Guilin City in 2025 under a conventional scenario and under a scenario with scenic spot expansion. Differences in land use patterns between the two scenarios were analyzed by pixel comparison and by landscape indices. [Results] ① Scenic spot expansion will reduce the reception pressure in tourism hot spots in Guilin City, but it would not be conducive to the urbanization of districts and counties close to the tourism hot spots. ② Scenic spot expansion would be conducive to the development of tourism in “growth poles”, such as Yangshuo and Xing'an County, and the influence of the “growth poles” would also impact most surrounding districts and counties, resulting in a greater expansion of construction land, but a smaller expansion of cultivated land. However, due to the scattered distribution of construction land in the north part of Guilin City, the radiations and driving factors among districts and counties would be relatively limited. Under the scenic spot expansion scenario, more rapid development of tourism in Xing'an, Quanzhou, and Longsheng County had no significant radiation and driving effects on tourism in Ziyuan and Guanyang County, but made these areas less competitive in construction land. ③ The landscape indices showed that scenic spot expansion would lead to more serious disturbance and occupation of agricultural and ecological space such as cultivated land, forest land, grassland, and shrubland. However, scenic spot expansion would promote protection of water bodies and wetlands, and the expansion of construction land would be more integrated. [Conclusion] Scenic spot expansion in Guilin City would reduce the reception pressure in tourism hot spots and promote the development of tourism in “growth poles” and most regions surrounding the “growth poles”. However, scenic spot expansion would not be conducive to the development of areas around tourism hot spots and areas that are relatively remote and not within the radiation ranges.